Unusual temperature dependence of salt effects for ``on water'' wittig reaction: hydrophobicity at the interface - Tiwari, Shraeddha; Kumar, Anil (Chemical Communications, 2008)
An unusual variation with temperature of the salt effects in aqueous Wittig reaction is observed, suggesting that hydrophobic acceleration of reactions comprising ``on water'' reactants is fundamentally different from that for reactions with small non-polar solutes.